Granulocytic Expression of CD11b/CD18 and Thrombotic Risk in Patients with Myeloproliferative Neoplasms - Doroteya Todorieva-Todorova; Katya Kovacheva; Nikolay Tzvetkov; Svetla Blazheva; Tzvetan Lukanov (Journal of Biomedical & Clinical Research)
Myeloproliferative neoplasms (MPN) are clonal hematological conditions characterized by excessive production of one or more cell lines in the bone marrow. The blood cells produced are often hyperactive in their functions, which could lead to complications in the disorder‘s clinical course. We aimed to define the role of granulocytic CD11b/CD18 expression for the thrombotic risk in MPN patients. We investigated 110 patients with a histologically confirmed diagnosis of a myeloproliferative disease and a control group of 46 healthy volunteers. In the patient group, we found an average expression 4.59 times higher than in the control group. The highest expression was found in a subgroup of patients with polycythemia vera – 71.55% of the patients’ neutrophils. In each subgroup with essential thrombocythemia, myelofibrosis, and chronic myeloid leukemia, the patients with a history of thrombotic complication had a higher expression than the patients without such complications.